2010
DOI: 10.1038/onc.2010.418
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of endoglin in tumor cell plasticity of Ewing sarcoma and melanoma

Abstract: Tumor cell plasticity enables certain types of highly malignant tumor cells to dedifferentiate and engage a plastic multipotent embryonic-like phenotype, which enables them to 'adapt' during tumor progression and escape conventional therapeutic strategies. This plastic phenotype of aggressive cancer cells enables them to express endothelial cell-specific markers and form tubelike structures, a phenotype that has been linked to aggressive behavior and poor prognosis. We demonstrate here that the transforming gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 40 publications
4
66
0
2
Order By: Relevance
“…Another study found that endoglin expression in Ewing sarcoma tumors is associated with increased expression of several proteins, including FAK, and is associated with poor outcome (38). Recently, a phosphoproteomics screen à , P < 0.05; Ãà , P < 0.01; ÃÃà , P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that endoglin expression in Ewing sarcoma tumors is associated with increased expression of several proteins, including FAK, and is associated with poor outcome (38). Recently, a phosphoproteomics screen à , P < 0.05; Ãà , P < 0.01; ÃÃà , P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Endoglin was also found to be expressed by tumor cells in Ewing sarcoma and melanoma. Endoglin expression in these two types of cancer correlated with tumor cell plasticity and participates in the formation of vascular-like structures (10). On the other hand; the strong expression of endoglin indicated a poor prognosis in gastric cancer (5).…”
Section: Discussionmentioning
confidence: 99%
“…For these high risk patients many markers have been suggested, but at present only classical markers, such as tumour location, are used in clinic [10]. EWS is recognised from the onset of its original description by James Ewing as a highly vascularised tumour and amongst many other pathways, chemokine and the TGF-B pathway might play a role for this excessive vascularisation pattern [11][12][13]. Besides angiogenesis, these pathways are involved in migration that might be reflected by the high metastatic propensity of EWS [1,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…EWS is recognised from the onset of its original description by James Ewing as a highly vascularised tumour and amongst many other pathways, chemokine and the TGF-B pathway might play a role for this excessive vascularisation pattern [11][12][13]. Besides angiogenesis, these pathways are involved in migration that might be reflected by the high metastatic propensity of EWS [1,13,14]. In several tumour types a positive correlation between increased expression of CXCR4 and metastatic propensity was reported, but contradictory results were reported in EWS [15][16][17].…”
Section: Introductionmentioning
confidence: 99%